Association between fish intake and prevalence of frailty in community-dwelling older adults after 4-year follow-up: the Korean frailty and aging cohort study - Ahn, Jeonghwan; Kim, Miji; Won, Chang Won; Park, Yongsoon (Frontiers in Nutrition, 2023)
Cross-sectional epidemiological studies suggested the intake of fish and seafood was negatively associated with the prevalence of frailty. This study aimed to investigate the hypothesis that the prevalence of frailty is negatively associated with the consumption of total seafood and fish at baseline and 4-year follow-up. Using a multicenter longitudinal study of community-dwelling Korean adults aged 70-84 years old, 953 participants at baseline and 623 participants at 4-year follow-up were included after excluding participants without data on frailty or dietary intake in the Korean Frailty and Aging Cohort Study. Frailty was defined using the Cardiovascular Health Study index, and participants with scores ≥3 were considered frail. The trained dietitians obtained two non-consecutive 24-hour dietary recalls during spring and fall at baseline. The prevalence of frailty was 13.5%. The intake of fish (OR 0.47; 95% CI 0.24-0.91; p for trend = 0.028) and total seafood (OR 0.34; 95% CI 0.18-0.68; p for trend = 0.002) at baseline was associated with frailty at 4-year follow-up after adjusting for the confounding factors. The intake of fish and total seafood at the baseline was negatively associated with the prevalence of exhaustion, low handgrip strength, and slow gait speed at 4-year follow-up. However, shellfish intake was not associated with frailty. In addition, the intake of fish, shellfish, and total seafood did not differ among the frailty transition groups in terms of deterioration, persistence, and reversal. The total consumption of seafood, particularly fish, could be beneficial for preventing frailty in Korean community-dwelling older adults. In particular, the consumption of fish (total seafood) at baseline could be beneficial for preventing exhaustion, low handgrip strength, and slow gait speed at 4-year follow-up.